2018
DOI: 10.1007/s00280-018-3606-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacokinetics and safety profile of single agent arsenic trioxide by continuous slow-rate infusion in patients with newly diagnosed acute promyelocytic leukemia

Abstract: Continuous slow-rate ATO infusion provided an alternative administration for ATO therapy with few toxic effects. Degree of methylation from MMA to DMA is inconsistent with that from iAs to MMA. PK of arsenic species is considered important for clinical use of ATO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…The results showed that As III in CSF was detected first, then MMA V or DMA V during administration, which was consistent with that in blood 16 . Our recent studies demonstrated that arsenic gradually accumulated with administration frequency in plasma and red blood cells from APL patients 16,17 . In this study, we found that the levels of As III , MMA V and DMA V in CSF increased substantially from Days 3 to 10, which suggested that arsenicals tended to accumulate with time in CSF in the initial treatment stage.…”
Section: Discussionsupporting
confidence: 84%
“…The results showed that As III in CSF was detected first, then MMA V or DMA V during administration, which was consistent with that in blood 16 . Our recent studies demonstrated that arsenic gradually accumulated with administration frequency in plasma and red blood cells from APL patients 16,17 . In this study, we found that the levels of As III , MMA V and DMA V in CSF increased substantially from Days 3 to 10, which suggested that arsenicals tended to accumulate with time in CSF in the initial treatment stage.…”
Section: Discussionsupporting
confidence: 84%
“…However, Sweeney et al found that the percentage of arsenic dose excreted as As III was reduced in patients with renal impairment . In our study, CL t of As III in the patient with AKI had no significant difference with that in patients with normal renal function (0.55 L/kg/h vs 0.6 L/kg/h), suggesting that renal elimination may not be the major way of clearance of As III . There are probably other pathways for the elimination of ATO.…”
Section: Discussioncontrasting
confidence: 68%
“…Since information on the effect of CVVHD on ATO dosing requirements is lacking, conventional administration with 0.16 mg/kg of ATO was chosen. Continuously slow‐rate infusion of ATO was conducted in this patient, as it achieves lower peak plasma concentrations of arsenic species and a favourable safety profile, which could be advantageous for critical ill patients. The clinical outcome for APL patients with CVVHD is equal to those without CVVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Five patients with newly diagnosed APL were intravenously administered at a dose of 0.16 mg/kg for 40 min infusion on the first day followed by 18–20 h daily at a very slow rate with an infusion speed of 8 drips/min ( Gao et al, 2018 ). All patients achieved hematologic complete remission after induction therapy, but also experienced side effects such as abnormal coagulation and anemia.…”
Section: Dna Methyltransferase Inhibitorsmentioning
confidence: 99%